The coevolution of industries and national institutions: Theory and evidence - J. Peter Murmann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
A survey across space and time reveals that leading firms operating in global industries often cluster in one or a few countries. The paper argues that nations differ in how successful they are in a particular industry because coevolutionary processes linking a particular industry and national institutions powerfully shape the path of an industry.s development. Across a wide range of contexts, scientific progress and industrial leadership reinforce each other in spirals of cumulative national advantage. A historical case study of synthetic dyes from 1857 to 1914 provides a dramatic example of how these positive feedback processes gave German organic chemistry and German dye firms a dominant position in the world. Over time, the relative strength of a nation in a particular industry and the capability of the country in a relevant scientific or engineering discipline display a strong positive correlation. Additional shorter case studies of agriculture, packaged software, and biotechnology support this induced hypothesis. We argue that the exchange of personnel between industry and academic institutions, the formation of commercial ties between them, lobbying on each other.s behalf and direct support from state agencies constitute causal mechanisms that can explain why successful firms often cluster in particular countries. – – Die führenden Unternehmen eines Industriezweiges konzentrieren sich, obwohl sie auf einem internationalen oder globalen Markt agieren, oft nur in einer eng begrenzten Anzahl von Ländern . oder in nur einem Land. Auf der Grundlage verschiedener Fallstudien werden in diesem Artikel spezifische Verknüpfungen von Industrie und national geprägter Wissenschaftslandschaft aufgezeigt, die in einem Prozess enger gegenseitiger Einflussnahme zu einer jeweils herausragenden . dominanten . wirtschaftlichen Position führten. Die Untersuchung der internationalen Dominanz Deutschlands auf dem Gebiet der Herstellung synthetischer Farbstoffe vor dem Ersten Weltkrieg zeigt eine starke positive Wechselwirkung zwischen der Forschung auf dem Gebiet der organischen Chemie und der Marktstellung der farbstoffproduzierenden Unternehmen. Der Aufstieg bedeutender Unternehmen wie Bayer, BASF und Hoechst steht dabei über personellen Austausch, kommerzielle Beziehungen und gemeinsames Lobbying in so enger Verbindung zu den relevanten akademischen Institutionen und ihrer Entwicklung, daß von einem koevolutionären Prozess gesprochen werden kann. Eine derartige positive Korrelation und ein daraus entstehender spezifischer Vorteil wird durch die Betrachtung des Marktes für Computer-Software oder des derzeit vieldiskutierten Bereichs der Biotechnologie untermauert.
Keywords: L10; O30; 330; Industry evolution; national institution; science-industry interface